Rhodium nanoparticles stabilized by ferrocenyl-phosphine ligands: synthesis and catalytic styrene hydrogenation. Issue 20 (25th April 2019) - Ibrahim, M.; Wei, M. M.; Deydier, E.; Manoury, E.; Poli, R.; Lecante, P.; Philippot, K.
Abstract : A series of ferrocenyl-phosphine ligands has been used to stabilize small rhodium nanoparticles that are active in the catalytic hydrogenation of styrene. Abstract : A series of ferrocenylphosphine-stabilized rhodium nanoparticles has been prepared in one pot from the organometallic [Rh(η 3 -C3 H5 )3 ] precursor. This complex has been decomposed by hydrogen treatment (3 bar) in dichloromethane in the presence of five different ferrocene-based phosphine ligands. Very small rhodium nanoparticles in the size range of 1.1–1.7 nm have been obtained. These nanoparticles have shown activity in a model catalytic reaction, namely the hydrogenation of styrene. These results evidence that the metal surface is not blocked despite the steric bulk of the stabilizing ligands. Moreover, certain selectivity has been observed depending on the ligand employed. To the best of our knowledge, such a type of compound has not yet been used for stabilizing metal nanoparticles and our findings highlight the interest to do so.